Palu City MSME Strategy to Face Data Leakage Risks and Digital Transformation Safely and Efficiently - Hidayat, M; Taufik, Taufik; Herdian, Freddy (Fakultas Seni Rupa dan Desain ITB, 2025)
The gap in digital technology adoption for operational purposes poses a significant barrier to the growth of MSMEs, particularly in Palu City. According to data from the central statistics agency or BPS-Statistics Indonesia of Central Sulawesi (2022/2023), only 13.42% of MSMEs utilize digital technology in their business activities. This study aims to identify the main obstacles in the digital transformation process of MSMEs by integrating the diffusion of innovation (DOI) theory and the technology acceptance model (TAM), as well as Islamic values and local cultural perspectives. Employing a qualitative case study approach, data sources include in-depth interviews with MSME actors in Palu City and related official documents. The data were analyzed using thematic analysis. The findings indicate that technological complexity, limited availability of skilled personnel, low digital literacy, and concerns about data breaches are the primary inhibiting factors. Local traditions such as nogae (cooperation) and cross-sector collaboration are identified as potential accelerators for promoting inclusive digital technology adoption. This study contributes theoretically by integrating sociocultural approaches into technology adoption models and by advocating for sustainable digital education strategies and collaborative cross-sector policies. The findings provide a foundation for formulating adaptive digital transformation strategies for MSMEs tailored to the local context.